Extensive tumoral melanosis associated with ipilimumab‐treated melanoma. (18th March 2016) - Staser, K.; Chen, D.; Solus, J.; Rosman, I.S.; Schaffer, A.; Cornelius, L.; Linette, G.P.; Fields, R.C.
Summary: Tumoral melanosis describes a pigmented lesion clinically similar to melanoma but on histology reveals dense aggregates of melanin‐laden, benign macrophages without malignant cells. In the few reported cases so far, tumoral melanosis has arisen in the skin or lymph node of a patient with a regressed melanoma or an epithelioid tumour. As a marker of regressed primary melanoma, its discovery may prompt investigation and surveillance for undiagnosed local or metastatic disease. Here, we present a unique case of extensive tumoral melanosis arising during ipilimumab treatment of in‐transit metastases from a previously excised melanoma. Abstract : What's already known about this topic? Limited tumoral melanosis occurs in the context of regressed melanoma. Ipilimumab activates the immune system and promotes tumour killing. What does this study add? This study shows tumoral melanosis to an extent previously not described. This extensive melanosis occurred in the context of ipilimumab treatment, suggesting that activated immunity may result in aggressive melanophagocytosis.